Al-Qa`ida Plays a Long Game in Syria - Lister, Charles
Since its public emergence in Syria in January 2012, the al-Qa`ida affiliate Jabhat al-Nusra has consistently sought to balance its transnational jihadist ideology and objectives with pragmatic efforts to integrate and embed itself within revolutionary dynamics. Maintaining this delicate balance has not been easy, but having succeeded to date, Jabhat al-Nusra is currently one of the most powerful and influential armed actors in Syria. Ultimately, however, the group is a wolf in sheep s clothing. It aims to establish durable roots in an unstable environment from which al-Qa`ida s transnational ambitions may one day be launched.
Keywords: Frente Al-Nusra; Terrorismo internacional; Siria